The affect of mentoring, management support and training and development on the employees' job performance - Rusli Nurdin; Awangku Hassanal Bahar Pengiran Bagul; Datu Razali Datu Eranza (2014)
This study analyzes the employment job performance by examining the relationship on mentoring, management support and training and development in State Federal Development Office of Sabah. Issues such as the complexity of the staffs from the different demographic and transformation of ICT systems give added insights to this study. The methodology for this study is using quantitative approach. The findings of this study reveal that mentoring, management support and training and development have significant positive relationship with job performance. This study recommends that human resource management in all over Sabah Development Office (SDO) in Malaysia should implement such practices in order to formulating and implementing strategies of employees’ job performance at the workplace.